4‐Benzothiazole‐7‐hydroxyindolinyl Diaryl Ureas Are Potent P2Y1 Antagonists with Favorable Pharmacokinetics: Low Clearance and Small Volume of Distribution. Issue 10 (2nd July 2014) - Qiao, Jennifer X.; Wang, Tammy C.; Hiebert, Sheldon; Hu, Carol H.; Schumacher, William A.; Spronk, Steven A.; Clark, Charles G.; Han, Ying; Hua, Ji; Price, Laura A.; Shen, Hong; Chacko, Silvi A.; et al.
Abstract Current antithrombotic discovery efforts target compounds that are highly efficacious in thrombus reduction with less bleeding liability than the standard of care. Preclinical data suggest that P2Y1 antagonists may have lower bleeding liabilities than P2Y12 antagonists while providing similar antithrombotic efficacy. This article describes our continuous SAR efforts in a series of 7‐hydroxyindolinyl diaryl ureas. When dosed orally, 4‐trifluoromethyl‐7‐hydroxy‐3, 3‐dimethylindolinyl analogue 4 was highly efficacious in a model of arterial thrombosis in rats with limited bleeding. The chemically labile CF3 group in 4 was then transformed to various groups via a novel one‐step synthesis, yielding a series of potent P2Y1 antagonists. Among them, the 4‐benzothiazole‐substituted indolines had desirable PK properties in rats, specifically, low clearance and small volume of distribution. In addition, compound 40 had high i.v. exposure and modest bioavailability, giving it the best overall profile.